Heightened risk of fatal police violence in and around reservations for American Indian/Alaska Native peoples in the United States - Gabriel L. Schwartz; Theresa Rocha Beardall; Jaquelyn L. Jahn (Proceedings of the National Academy of Sciences, 2026)
Fatal police violence is a public health problem in the United States, with large racial and spatial inequities that remain understudied. Indigenous people, for example, experience some of the highest rates of fatal police violence of any racial/ethnic group. Residents of American Indian/Alaska Native (AIAN) reservations may be at particular risk, given geographically specific police surveillance, jurisdictional mazes, and structural disinvestment. Yet little quantitative work has examined fatal police violence against Indigenous peoples in the United States, including by reservation geography. We examined whether AIAN people experience higher rates of fatal police violence in and around reservations at the population level. We analyzed data on all AIAN people killed by police (n = 203, 2013–2024) from the Mapping Police Violence database. We first summarized their geographic distribution and characteristics using descriptive statistics. We then estimated rate ratios using quasi-Poisson regression models with population offsets, comparing AIAN peoples’ fatal police violence rates in and around reservations versus farther away. We find that fatal police violence against AIAN people is strongly concentrated in and around reservations: 73% of AIAN deaths occurred on or within 10 miles of reservations, despite only 39 to 51% of the AIAN population living there. Those areas’ residents were 1.60 to 5.84 times more likely to be killed by police than those living farther away, depending on location and choice of population offsets. Sensitivity analyses indicated these elevated risks could not plausibly be explained away by differential racial/ethnic misclassification. A coordinated public health response to police violence is urgently needed in Indian Country.